2019
DOI: 10.1590/s1678-9946201961028
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the detection and molecular characterization of Cryptosporidium with emphasis in Brazilian studies: a review

Abstract: Cryptosporidium spp. is a pathogenic protozoan present in the gastrointestinal tract of several hosts. This protozoan was originally classified as within the Coccidia Class and has recently been reclassified to gregarine based on studies that observed the evolutionary phases from the process of excision and sequencing of the 18S rRNA gene. Molecular biology techniques have become diagnostic tools and have also been used to understand the epidemiology of Cryptospori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 94 publications
1
46
1
2
Order By: Relevance
“…To date, 38 species of Cryptosporidium have been identified in diverse hosts, totaling more than 40 subtypes infecting mammals (22)(23)(24). Among these, C. hominis and C. parvum are the main pathogens infecting humans and responsible for approximately 90% of human cryptosporidiosis (25).…”
Section: Discussionmentioning
confidence: 99%
“…To date, 38 species of Cryptosporidium have been identified in diverse hosts, totaling more than 40 subtypes infecting mammals (22)(23)(24). Among these, C. hominis and C. parvum are the main pathogens infecting humans and responsible for approximately 90% of human cryptosporidiosis (25).…”
Section: Discussionmentioning
confidence: 99%
“…To date, at least 38 species of Cryptosporidium spp. have been recognized by molecular characterization ( 39 41 ), with 73 genotypes ( 42 44 ) and 17 species having been identified in humans ( 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…They include the use of faecal smears stained by the modified Ziehl-Neelsen technique, Enzyme-linked immunosorbent assays (ELISA) and polymerase chain reaction (PCR) assays [13][14]. A comprehensive overview into the detection and molecular characterization of Cryptosporidium has been described elsewhere [15] The above mentioned methods have drawbacks such as being time-consuming and relatively expensive, as well as requiring well-equipped laboratories and well-trained or skilled personnel [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…CGE, Crypto/Giardia Duo-Strip, RIDA QUICK Cryptosporidium/Giardia/Entamoeba Combi and Giardia/Cryptosporidium Quik Check the authors observed varying sensitivities ranging from 92 to 100% and 100% specificities for all RDT brands for the detection of Cryptosporidium when compared to ELISA, microscopy, and qPCR as gold standards [17]. In addition, these RDTs demonstrate varying performances, and some of them are not well validated for the detection of less frequent non-parvum/hominis Cryptosporidium species [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation